CLIFF-GRADS awards scholarships to 46 Ph.D. fellows from the global south - Villarino, Maria Eliza J. (CGIAR System Organization, 2022)
The Climate, Food and Farming, Global Research Alliance Development Scholarships Programme (CLIFF-GRADS) announced 46 new awardees from low- and middle-income countries. CLIFF-GRADS is a joint initiative of the Global Research Alliance on Agricultural Greenhouse Gases (GRA) and the One CGIAR Mitigate+ Initiative on Research for Low-Emission Food Systems. CLIFF-GRADS is an excellent program for building global scientific expertise to address the need for shared effort in addressing climate change,” said Deborah Knox, manager of the GRA Secretariat.